The CCT domain-containing gene family has large impacts on heading date, regional adaptation, and grain yield in rice - Jia ZHANG; Yong HU; Li-he XU; Qin HE; Xiao-wei FAN; Yong-zhong XING (Journal of Integrative Agriculture, 2017)
There are 41 members of the CCT (CO, CO-like, and TOC1) domain-containing gene family in rice, which are divided into three subfamilies: COL (CONSTANS-like), CMF (CCT motif family), and PRR (pseudoresponse regulator). The first flowering gene to be isolated by map-based cloning, Heading date 1 (Hd1), which is the orthologue of CO in rice, belongs to COL. The central regulator of plant development, Ghd7, belongs to CMF. The major role in controlling rice distribution to high latitudes, Ghd7.1/PRR37, belongs to PRR. Both of Hd1, Ghd7 and Ghd7.1 simultaneously control grain number, plant height, and the heading date. To date, 13 CCT family genes from these three subfamilies have been shown to regulate flowering. Some of them have pleiotropic effects on grain yield, plant height, and abiotic stresses, and others function as circadian oscillators. There are two independent photoperiod flowering pathways that are mediated by GI-Hd1-Hd3a/RFT and GI-Ehd1-Hd3a/RFT in rice. CCT family genes are involved in both pathways. The latest study reveals that protein interaction between Hd1 and Ghd7 integrates the two pathways. CCT family genes are rich in natural variation because rice cultivars have been subjected to natural and artificial selection for different day lengths in the process of domestication and improvement. Alleles of several crucial CCT family genes such as Hd1, Ghd7, and Ghd7.1 exhibit geographic distribution patterns and are highly associated with yield potentials. In addition, CCT family genes are probably involved in the responses to abiotic stress, which should be emphasized in future work. In general, CCT family genes play important roles in regulating flowering, plant growth, and grain yield. The functional identification and elucidation of the molecular mechanisms of CCT family genes would help construct a flowering regulatory network and maximize their contribution to rice production.